Crop Diversification in Rangpur Region (Bangladesh Rice Journal, 2018)
For the planning of future research and development elaborate information and a reliable database on existing cropping patterns, cropping intensity and crop diversity of a particular area are of prime importance for guiding policy makers, researchers, extensionists and development workers. A massive group work was accomplished over all 35 upazilas of Rangpur region during 2016 using pre-tested semistructured questionnaire with a view to document the existing cropping patterns, cropping intensity and crop diversity in the area. Boro−Fallow−T. Aman occupied the largest portion (53%) of net cropped area (NCA) with its distribution in all upazilas. The second largest area, 5% of NCA, was covered by Maize−Fallow−T. Aman which was spread out over 23 upazilas. Under the current investigation 134 cropping patterns were identified. The highest number of cropping patterns was identified 31 in Badarganj of Rangpur and the lowest was 10 in Razibpur of Kurigram district. The highest value of CDI was observed 0.991 in Razibpur upazila followed by 0.989 in Chilmari of Kurigram. The range of cropping intensity values was recorded 190-255%. The maximum value was for Gangachara upazila of Rangpur and minimum for Gaibandha sadar upazila. The overall CDI of Rangpur region was calculated 0.871 and the average cropping intensity at regional level was 219%.Bangladesh Rice j. 2017, 21(2): 255-271